The Effect of Fatigue Management, Training, Reward Systems, and Information Technology on Occupational Safety Performance - Nanang Sofal Jamil; Istiatin Istiatin; Sudarwati Sudarwati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The purpose of this study was to determine the simultaneous and partial effects of the variables Fatigue Management, Training, Reward Systems, and Information Technology on Occupational Safety Performance in the transportation industry at PT. KAI Central Daop Jakarta. This study took place at the PT. KAI Central Daop Jakarta office. This was a quantitative study, with data collection using a questionnaire. The sample consisted of 50 employees in the Occupational Safety and Health (K3) department. Data analysis techniques used were multiple regression, F-test, t-test, and test of determination (R2). Fatigue management influences the Occupational Safety Performance of PT. KAI Central Daop Jakarta employees. Training influences the Occupational Safety Performance of PT. KAI Central Daop Jakarta employees. The Reward System influences the Occupational Safety Performance of PT. KAI Central Daop Jakarta employees. Information Technology influences Occupational Safety Performance of PT. KAI Central Operation Office Jakarta Employees.